Multiculturalism and Conflict Reconciliation in the Asia-Pacific - Shimizu, Kosuke (Palgrave Macmillan, 2014)
This book is open access under a CC BY license. Japan has recently promoted a number of initiatives that can be termed an opening to the world and the Asia-Pacific in particular. These have origins in Japan's globalization generally and multicultural policies more specifically. The chapters in this book are grouped in three parts-theories, language, and migration-and they explicate details of multiculturalism in the Asia-Pacific, largely focused on Japan, but including cases that extend beyond Japan as well. Alternative understandings based on analyzing conflicts and moving towards reconciliation underscore the urgency of viewing multiculturalism in Japan and the Asia-Pacific from perspectives that are firmly based in the region. Themes such as immigration, identity, foreign language education, politics and language, English language policies, dual citizenship, foreign labor policies and movements, and higher education are all addressed in the individual chapters. This book will be of interest to scholars of multiculturalism in a wide variety of fields.